Penggunaan Energi Surya sebagai Tenaga Penggerak Mesin Pencacah Hijauan Pakan Ternak di Dusun Turi, Tulungagung - Hariyo Priambudi Setyo Pratomo; Hanny Hosiana Tumbelaka; Joni Dewanto; Indar Sugiarto; Iwan Halim Sahputra (Institut Pertanian Bogor, 2025)
This community service activity aimed to apply solar energy to a cow and goat fodder chopper to obtain finely chopped forage. The realization of chopper and small-scale solar power plants was based on interviews with farmers. Chopped forage included elephant grass, caliandra, and young sugarcane. The electric power plant and chopper were settled in an area agreed upon by the farmers. Moreover, a comparative study on chopper construction shows that the free cutting mechanism implemented is also used by other researchers and has a simple and strong construction, nevertheless providing ease in disassembly and maintenance. A 12,1568 m2-monocrystalline solar panel, inverter, and battery were employed as the electric energy generating station for powering the chopper. The electric current surge occurring at the start of the chopper operation was found to be 73.82 A and can be dampened by a variable-speed drive to 3.4 A. The electric power station has an installed capacity of 5000 Watts and can deliver effective electric energy of 3000 Watts from an 8 hour-shining time of sunlight (8 a.m to 16 p.m) every day. The chopper can deliver a production capacity of fine chopped fodder of 200 kg/hour and can be operated for 6 hours nonstop daily. Farmers were satisfied with the performance of the chopper, as shown in the feedback forms of the farmers. Additionally, farmers have learned the benefits of the machine and have been able to employ it as well as to do chopper maintenance. This study successfully reached the capacity change of ruminant farmers in Turi Hamlet.